Theoretical Evidence behind Bifunctional Catalytic Activity in Pristine and Functionalized Al2C Monolayers. Issue 1 (13th December 2017) - Almeida, Roseley; Banerjee, Amitava; Chakraborty, Sudip; Almeida, Jailton; Ahuja, Rajeev
Abstract: First principles electronic structure calculations based on the density functional theory (DFT) framework are performed to investigate hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) on two‐dimensional Al2 C monolayers. In addition to the pristine Al2 C monolayer, monolayers doped with Nitrogen (N), Phosphorous (P), Boron (B), and Sulphur (S) are also investigated. After determining the individual adsorption energy of hydrogen and oxygen on the different functionalized Al2 C monolayers, the adsorption free energies are predicted for each of the functionalized monolayers in order to assess their suitability for HER or OER. The density of states and optical absorption spectra calculations along with the work function of the functionalized Al2 C monolayers enable us to gain a profound understanding of the electronic structure for the individual system and their relation to the water splitting mechanism. Abstract : Doping the catalyst : Functionalization of Al2 C monolayers with non‐metallic dopants (B, N, P and S) leads to bifunctional catalytic activity without compromising the stability or the planarity. Boron and nitrogen have emerged as promising dopants for this 2D material for hydrogen and oxygen evolution reaction through water splitting. Our results suggest that boron and nitrogen could also be envisaged as the promising elemental dopants for other 2D materials.